Lessons for Medical and Health Education Learned from the COVID-19 Pandemic - Gardanova, Zhanna; Belaia, Olga; Zuevskaya, Svetlana; Turkadze, Klavdiya; Strielkowski, Wadim (Healthcare (Basel, Switzerland), 2023)
Our paper analyzes lessons for medical education and health education stemming from the experience gained in the course of the COVID-19 pandemic. Moreover, it tackles the issue of the social health and psychological wellbeing of medical students involved in online education during the COVID-19 pandemic. The paper systematizes up-to-date data on how medical schools and universities have adapted to the conditions of the COVID-19 pandemic and implemented novel effective solutions for the learning process, such as transitioning from traditional in-person classes to online learning, incorporating virtual simulations and telemedicine experiences for clinical training, and collaborating with health authorities to provide support in testing and contact tracing efforts. The paper contains an analysis of various aspects of medical education, such as the changes in practical classes, the impact of the pandemic on the formation of communication skills, methods for assessing students' knowledge and skills, and many others. It also considers case studies related to the implementation of educational programs, methodologies, and novel digital technologies in a pandemic. Additionally, the paper features an empirical study that is based on the results of our own survey that was carried out with the help of a snowball convenient sampling that involved 710 medical students between 19 and 25 years of age (56% females and 44% males) from 4 Russian regions (Moscow, Krasnodar, Kazan, and Saint Petersburg). We applied the correlation between stress scores, anxiety scores, factors of stress, and strategies for coping with stress and various economic and demographic variables (age, environment, and gender) that were analyzed using the chi-square test. Our results demonstrate that over 85% of the students in our sample yielded an above-average vulnerability to stress due to the COVID-19 restrictions. At the same time, around 61% of the students experienced severe anxiety during online education in the COVID-19 pandemic. The important factors leading to stress and anxiety were the fear of getting infected and social distancing, and the best strategy to deal with stress and increase wellbeing was self-control. Through a comprehensive review of the literature and empirical estimations, our paper identifies key areas of improvement, including curriculum adaptation, technology integration, faculty development, student support, and interprofessional collaboration. The proposed recommendations aim at strengthening medical education systems and preparing healthcare professionals to effectively navigate future pandemics.
Keywords: digital technologies; anxiety; COVID-19 pandemic; wellbeing; medical education; health education